Clinical features of multiple primary carcinomas of the oral cavity - Li, Ya-Dong (Exp Ther Med, 2017)
The present study aimed to elucidate the clinical characteristics of multiple primary carcinomas of the oral cavity. The clinical records of 1,024 patients who were treated during follow-up for oral cancer at the Department of Stomatology, Henan Provincial People's Hospital, between March 2013 and December 2014 were retrospectively reviewed. The clinical characteristics of 961 patients who developed single primary oral squamous cell carcinoma (SCC) during follow-up and 54 patients who subsequently developed multiple primary carcinomas in the oral cavity were compared. Multiple primary carcinomas exhibited a female predilection, were most prevalent in the gingiva, and tended to show earlier tumor and nodal stages, as compared with single primary carcinomas. The local recurrence rate was higher for multiple primary carcinomas, as compared with single primary carcinomas, and was demonstrated to increase with the number of multiple primary occurrences. The cumulative incidence rates for metachronous second primary carcinomas following the onset of the first carcinoma at 10 years was 8.0%. Recurrence of multiple primary carcinomas did not decrease the survival rates of the patients assessed in the present study. Furthermore, differences were detected in the clinical characteristics between patients with single oral SCC and those with multiple primary oral carcinomas. The results of the present study indicated that early diagnosis and treatment and close long-term follow-up are required for patients with multiple primary oral carcinomas.